Proceedings of the 25th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (IEEE Cat. No.0
DOI: 10.1109/iembs.2003.1280419
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of surface electrode-array electromyogram of biceps brachii muscle in voluntary isometric contraction

Abstract: Abstruct-The study of the electric signals generated by contracting muscle fibers (EMG) is relevant to neurophysiological research and to the diagnosis of motoneuron diseases. Classical diagnosis methods make use of invasive, painful needle electrodes. We explored a non-invasive alternative to these methods by developing a specific algorithm that uses Independent Component Analysis OCA) and template-matching techniques to decompose surface EMG (s-EMG). An experiment was carried out with two healthy subjects pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This might be the reason why when using real s-EMG signals we do not get results as accurate as those obtained when using synthetic s-EMG [17]. For some of the independence measures it was necessary to estimate both joint and marginal probability density function (p.d.f.)…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…This might be the reason why when using real s-EMG signals we do not get results as accurate as those obtained when using synthetic s-EMG [17]. For some of the independence measures it was necessary to estimate both joint and marginal probability density function (p.d.f.)…”
Section: Resultsmentioning
confidence: 75%
“…In order to measure the MUAP waveforms enhancement of a target MUAPT compared to the other MUAPTs obtained by applying ICA, we designed and applied to all the data obtained an additional measure; the peak-to-peak signal-to-interference ratio (SIR pp ) [17]. This measure was defined as the mean value of a MUAPT N firings peak in its closest channel (where it appeared the strongest) divided by the mean of the N strongest peaks belonging to the other MUAPTs present in the same channel.…”
Section: Ica Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a rectangular window is used then Equation 3 is an LPD filter. Similarly to the LPD filter the WLPD is very easy to implement and considerably fast for real-time applications, but results presented in [17,46] show that phase distortion may be present in the filtered signal and depending on the level of noise false spikes may be generated.…”
Section: Weighted Low-pass Differential Filtermentioning
confidence: 99%
“…In fact, when studying the state of deep muscles this is the only possible choice. However, many studies [5,11,17,43,49] have shown that surface EMG electrodes with a sufficiently small contact surface may be successfully applied to the detection of MUAP activity in superficial muscles.…”
Section: Signal Detection and Acquisitionmentioning
confidence: 99%